The power of sunspots: An experimental analysis - Dietmar Fehr; Frank Heinemann; Aniol Llorente-Saguer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
This paper presents an experiment on a coordination game with extrinsic random signals, in which we systematically vary the stochastic process generating these signals and measure how signals affect behavior. We find that sunspot equilibria emerge naturally if there are salient public signals. However, highly correlated private signals can also lead to sunspot-driven behavior, even when this is not an equilibrium. Private signals reduce the power of public signals as sunspot variables. The higher the correlation of extrinsic signals and the more easily they can be aggregated, the more powerful these signals are in distracting actions from the action that minimizes strategic uncertainty.
Keywords: C92; D82; D83; E39; E58; 330; coordination games; strategic uncertainty; sunspot equilibria; forward guidance; expectations